Interactive Effects of Feed Form, and Fiber Source and Levels on Production Performance, Foregut Development, and Nutrients Utilization in Broilers - A Rasool; SN Qaisrani; A Khalique; J Hussain (Brazilian Journal of Poultry Science)
ABSTRACT A total of 480 one-day-old straight-run broilers were used to evaluate the effects of feed form (FF), fiber source (FS), and fiber level (FL) on production performance, foregut development, gut histomorphology, apparent ileal digestibility (AID) of amino acids (AA) and cecal microbiota count. Eight experimental diets comprising 6 replicates with 10 birds each were tested in a 2 × 2 × 2 factorial arrangement in a completely randomized design using two FF (Pellet vs. Mash), two FS (Oat hulls (OH) vs. Sugarcane bagasse (SCB)) and two FL (3 vs. 5%). Overall (0-35 days), broilers fed OH pelleted diet had better (p< 0.05) feed intake, body weight gain and FCR than those fed SCB pelleted or mash diets. Broilers fed OH pelleted diet showed improved VH (villus height) by 5% and VCR (villus height to crypt depth ratio) up to 13%. An interaction (p<0.05) between FS × FF was detected for lysine, methionine, threonine, valine, arginine and cysteine. The pelleted diet decreased (p<0.05) the empty relative weight of proventriculus and gizzard. Pelleted diet containing OH increased cecal Lactobacillus spp.. and reduced E. Coli count in comparison to mash OH and SCB. In conclusion, 3% OH in pelleted diets may potentially be used in broiler diets to enhance duodenal histomorphology, nutrients digestibility, beneficial cecal microbiota count, and production performance.